Relationship of lifestyles with the physical condition of adolescents aged 15 to 17 years of the Alfonso López Pumarejo Departmental Educational Institution of Nemocón (Cundinamarca-Colombia) (Impetus, 2021)
The physical condition represents an important indicator of the health status of an individual, which is closely related to the lifestyle adopted in the different stages of development of the human being. The present study performs the analysis of lifestyles and physical condition to 166 adolescents between 15 and 17 years old; 82 women and 84 men, who delivered informed consent and assent, to then apply the FANTASTIC QUESTIONNAIRE that divides lifestyles into 10 dimensions (Family, Activity, Physics, Nutrition, Tobacco, Alcohol, Sleep and Stress, Personality Type, Interior Image, Control of sexuality, Order and grooming), and the physical condition by means of the application of the ALFA FITNESS GRAM test battery which evaluates 4 components of the physical condition (Cardiorespiratory capacity, skeletal muscle capacity, motor coordination and body composition). The data were entered in Excel 2016 and processed in SPSS V 2.1 to determine which of these dimensions affects to a greater or lesser degree the physical condition of the adolescent. Normality tests were performed and the Sperman correlation test was used. It is found that there are significant correlations between lifestyles and physical condition in women, mainly in the dimensions that involve inter and intrapersonal relationships with body composition and the manual pressure force, in men no significant correlations are found and those that are weak, indicating that apparently lifestyles they do not directly affect the physical condition of the adolescent man, which may be due to morphological physiological changes typical of the stage of development of puberty.